The gas-loss evolution in dwarf spheroidal galaxies: Supernova feedback and environment effects in the case of the local group galaxy Ursa Minor. Issue Volume 15:Issue S359(2020) (March 2019) - Caproni, Anderson; Lanfranchi, Gustavo Amaral
Abstract: In this work, we performed two distinct non-cosmological, three-dimensional hydrodynamic simulations that evolved the gas component of a galaxy similar to the classical dwarf spheroidal galaxy Ursa Minor. Both simulations take into account types II and Ia supernovae feedback constrained by chemical evolution models, while ram-pressure stripping mechanism is added into one of them considering an intergalactic medium and a galactic velocity that resemble what is observed nowadays for the Ursa Minor galaxy. Our results show no difference in the amount of gas left inside the galaxy until 400 Myr of evolution. Moreover, the ram-pressure wind was stalled and inverted by thermal pressure of the interstellar medium and supernovae feedback during the same interval.